ChemInform Abstract: Chemical‐Looping Combustion and Gasification of Coals and Oxygen Carrier Development: A Brief Review. Issue 13 (March 2016) - Wang, Ping; Means, Nicholas; Shekhawat, Dushyant; Berry, David; Massoudi, Mehrdad
Abstract: Review: 95 refs.